Co-processed excipients: a revisit of its development in the past two decades; a review - Liew, Kai Bin; Hii, Shou Hui; Helal Uddin, A.B.M.; Sarker, Zaidul Islam; Chew, Yik Ling (Wolters Kluwer Health, 2022)
A pharmaceutical excipient is a substance acts as a carrier incorporates active pharmaceutical ingredients. Excipient selection focuses on desirable characteristics of excipients. Limitations of using excipients which affect the characteristics of the granules and tablets. Co-processed excipients are produced by integrating one excipient into the other excipient at particle level. Such combination of two or more pharmacopeial or non-pharmacopeial excipients does not involve chemical reaction and only involve physical properties changes which is not possible by simple physical mixing. The introduced multicomponent-based excipients for formulation to obtain better features and tableting properties. The objectives of this revisit to discuss the development of co-processed excipients in the past two decades. This review summarizes the advantages of co-processed excipient, the manufacturing process, compilation of co-processed excipients in the literature, limitations, evaluation methods and future development of co-processed excipient. Co-processed excipients will undoubtedly attract attention from academia and pharmaceutical industry as more newer combinations of excipients and newer ways of co-processing become available Besides, rather using numerous excipients in formulation, it allows for the development and usage of single multifunctional excipients.